Two-dimensional kinematics and stellar populations of early-type galaxies: First results from the SAURON survey - Bacon, R; Bureau, M; Cappellari, M; Copin, Y; Davies, R; Emsellem, E; Kuntschner, H; McDermid, R; Miller, B; Peletier, R; Verolme, E; de Zeeuw, T (2002)
We present the SAURON project, which is aimed at studying the morphology, two-dimensional kinematics and stellar populations of a representative sample of elliptical galaxies and spiral bulges.SAURON, a dedicated integral-field spectrograph that is optimized for observations and has high throughput, was built in Lyon and is now operated at the WHT 4.2m telescope. At present, we have ob served approximately two thirds of the seventy-two sample galaxies with SAURON. A comparison with published long-slit measurements demonstrates that the SAURON-data are of equal or better quality, and provides full two-dimensional coverage. The velocity and velocity dispersion fields exhibit a large variety of morphologies: from simple rotating systems to cylindrical, disky and triaxial velocity fields, bars and decoupled cores. Most of these kinematical signatures do not have counterparts in the light distribution. While some galaxies are consistent with axisymmetry, most Are more complex systems than assumed previously. This suggests that the kinematical properties of nearby E/S0 galaxies do not agree with the often assumed simplistic two-family model, in which the giant non-rotating triaxial ellipticals are opposed to the fast-rotating axisymmetric faint ellipticals and S0s.